2011
DOI: 10.4103/1658-354x.82811
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent intrathecal injection of atracurium

Abstract: This report relates how tracurium was given by mistake, intrathecally, during spinal anesthesia, to a 38-year-old woman, who was a candidate for abdominal hysterectomy. When no analgesia was observed, the mistake in giving the injection was understood. She was evaluated postoperatively by train of four ratio, measuring her breathing rate, eye opening, and protruding of tongue at one, two, twenty-four, and forty-eight hours, and then at one and two weeks, with the final evaluation the following month. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to the studies, inadvertently intrathecal injection of atracurium causes signs and symptoms such as tachycardia, hypotension, and diplopia (18,19). However, two cases of inadvertently intrathecal injection of atracurium have been reported that did not show hemodynamic symptoms and complications (20,21). According to reports, high-dose intravenous injection of atracurium causes seizure (19).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…According to the studies, inadvertently intrathecal injection of atracurium causes signs and symptoms such as tachycardia, hypotension, and diplopia (18,19). However, two cases of inadvertently intrathecal injection of atracurium have been reported that did not show hemodynamic symptoms and complications (20,21). According to reports, high-dose intravenous injection of atracurium causes seizure (19).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…One of the challenging problems in the operating room is accidental injection of drugs in epidural and subarachnoid spaces. It can be safe such as labetalol and atracurium[ 1 2 ] to even death following injection of vindesine or[ 3 ] bortezomib. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Inadvertent subarachnoid or subcutaneous injection of nondepolarizing muscle relaxants has been reported. [ 4 ] In a study by Iwasaki et al ., peak effect of pancuronium was much faster in intravenous injection and recovery time was longer after subcutaneous injection. [ 5 ]…”
mentioning
confidence: 99%